Humphrey Carver and the Federal Government’s Postwar Revival of Canadian Community Planning - Gordon, David (Urban History Review / Revue d'histoire urbaine, 2018)
Humphrey S.M. Carver (1902–1995) played an important role in the federal government’s revival of Canadian community planning following the Second World War and guiding Canada’s transformation into a suburban nation. Carver was a senior executive at Central Mortgage and Housing Corporation (CMHC) from 1948 until his retirement in 1967. While Carver’s work as a housing advocate is well documented, his role as an advocate for community planning is less known. He was the founding vice-president of the Community Planning Association of Canada (CPAC) in 1947, president of the Town Planning Institute of Canada (TPIC), 1963–4, and a vice-president of the American Society of Planning Officials. While at CMHC, he assisted in the rapid national expansion of the CPAC and the 1953 resuscitation of the TPIC. His agency funded the establishment of the first five Canadian planning schools, hundreds of planning scholarships, and millions of dollars in planning research and planning studies.